Persepsi Pasien Tuberkulosis Paru tentang Peran Perawat sebagai Edukator di Wilayah Kerja Puskesmas Kabupaten Banyuwangi - Latifah, Umi; Ardiana, Anisah; Purwandari, Retno; Asmaningrum, Nurfika; Kurniawan, Dicky Endrian (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
Pulmonary tuberculosis has become a world emergency disease, so it is necessary to treat TB transmission from patients. Therefore, knowledge about pulmonary TB itself is needed. In this case the nurse acts as an educator in the form of essential nursing care. The purpose of this study was to analyze the description of the role of nurses as educators based on the perceptions of pulmonary TB patients at the two Puskesmas Banyuwangi Regency and the characteristics of the patients. The method used is descriptive analysis method with a sample of 73 pulmonary tuberculosis patients and the sampling technique is purposive sampling. Data collection was carried out using a questionnaire on the role of the nurse as an educator. The results showed that the role of nurses as educators 68.5% stated well, the average patient with a length of treatment of 4 months and an average age of 38 years. And the majority of patient education is high school, namely 43 patients. Most of the patients were 58.2% male and 78.1% of patients who did not have a family with pulmonary TB disease. Patients who have relapsed TB are 4% less than patients who have never had TB before, 94.5%. It is hoped that nurses can maintain their role as educators to stop TB transmission through health education